2013
DOI: 10.4236/ajps.2013.43065
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites from Resistant and Susceptible <i>Pinus thunbergii</i> after Inoculation with Pine Wood Nematode

Abstract: Pine wilt disease (PWD), which is caused by pine wood nematodes (PWN), is one of the most serious forest diseases worldwide. To clarify the mechanism of resistance to PWD, we compared metabolites from resistant and susceptible Japanese black pine (Pinus thunbergii) families after inoculation with PWN. After 2 weeks to 1 month post inoculation, the number of PWN dramatically increased in susceptible plants, but not in resistant plants. At this PWN-proliferation phase, ethyl acetate soluble fractions extracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Remarkably, strain BXF1 is also able to grow in the presence of high concentrations of toluene, xylene, benzoic acid (BA), phenylacetic acid (PAA) and phenol, and uses BA and PAA as sole carbon sources (Supporting Information Table S2). BA and PAA were found to be linked to PWD development as they are found in abundance in the wilting pine (Oku, ; Kawazu et al ., ; Zhang et al ., ). Oku () suggested that these compounds could act as phytotoxins since their application in healthy pine seedlings led to PWD symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, strain BXF1 is also able to grow in the presence of high concentrations of toluene, xylene, benzoic acid (BA), phenylacetic acid (PAA) and phenol, and uses BA and PAA as sole carbon sources (Supporting Information Table S2). BA and PAA were found to be linked to PWD development as they are found in abundance in the wilting pine (Oku, ; Kawazu et al ., ; Zhang et al ., ). Oku () suggested that these compounds could act as phytotoxins since their application in healthy pine seedlings led to PWD symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Some particular phenolic compounds found in resistant pine species, i.e., stilbenoids, have been reported to show nematicidal activity to the PWN in in vitro assays (Suga et al 1993), although their role as a factor of resistance in vivo has been questioned (Zhang et al 2013). On the other hand, phenolic compounds are also known to accumulate in response to the PWN infections when compared to control trees (Futai 2003).…”
Section: Treesmentioning
confidence: 99%
“…Some examples that contradicted this were also reported, however, indicating that migration and colonization ability do not completely determine the susceptibility of pines to the PWN (Mori et al 2008;Eo et al 2011). The accumulation of chemical defensive compounds that repeal, immobilize or disrupt the life cycle and reproduction of nematodes (Suga et al 1993;Hanawa et al 2001;Zhang et al 2013), and the ability to activate defensive responses to the infection (Ichihara et al 2000b), may also play a key role. Reduced nematode migration and proliferation rates within the plant tissues seem to be crucial for pine resistance to the PWN (Kuroda 2008b).…”
mentioning
confidence: 99%
“…Pine wilt disease (PWD) is one of the most serious diseases [1,2] that affects coniferous forests around the world and it is considered to be caused by pine wood nematodes (PWNs), Bursaphelenchus xylophilus (Steiner & Buhrer) Nickle [3,4]. In Asia, PWD was introduced into Japan during the early 20 th century [5] and it spread subsequently to other countries, including China [6] and Korea [7], where pine trees have no natural resistance to B. xylophilus .…”
Section: Introductionmentioning
confidence: 99%